KEBIJAKAN HUKUM PIDANA DALAM UPAYA PENANGGULANGAN TINDAK PIDANA IMIGRAN ILLEGAL - MOHAMMAD AZIZUN HAKIM , Eko Soponyono, Purwoto (Diponegoro Law Journal, 2012)
Formulation of the Law No. 6 of 2011 basically to accommodate any issues that arise in the field of immigration. Issues such as illegal immigrant crime, criminal forgery travel, and human trafficking. Explanation of illegal immigrants does not come clearly in the law, but can be encountered in the editorial section 113 is meant to crack down on those involved in the criminal illegal immigrants.   This  study  uses  normative  juridical,  by  reviewing  /  analyzing  secondary  data, particularly primary legal materials in the form of legislation and secondary legal materials in the form of the Migration  Act  1958 in Australia and the Law of Malaysia Act 574 Penal Code.   From  these  results  it  can  be  concluded  that  the  formulation  of  criminal  illegal immigrants in  Act No. 6 of 2011 on Immigration is not enough to accommodate all the problems  in  immigration  crime,   particularly  in  the  case  of  illegal  immigrants.  Some disadvantages formulation criminal offenses related to illegal immigrants in the law relating to the qualification of crime is still unclear qualifications included in the violation or crime. Several weaknesses in this legislation can be improved in the future by considering  the setting  in  some  countries  by  comparing  the  law  specifically  governing  criminal  illegal immigrants.   In line with the enactment of Law No. 6 of 2011 on Immigration is expected that this study also  helped provide input in the formation undng laws that specifically criminalize illegal immigrants in the future.